A colloidal battery internal formation process
Through vacuum infusion and low current density combination with constant voltage charging, a sheet-type felt PVC partition and foot pad are used to form an electrolyte diffusion channel to realize the direct internalization of colloidal batteries, solving the existing complicated processes and waste acid problems. Realize zero waste acid emissions and environmentally friendly production.
Patent Information
- Application Number
- CN202411449007.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-17
AI Technical Summary
The existing colloidal batteries have complex production processes, producing a large amount of waste acid, which has huge environmental pressure and management costs, and lacks process innovation.
The acid-containing colloidal electrolyte is added by vacuum infusion, combined with low current density formation and constant voltage charging, and the electrolyte diffusion channel is formed through a sheet-type felt PVC separator and foot pad to achieve direct internalization of the colloidal battery.
It realizes zero waste acid emissions of colloidal batteries, simplifies production processes, reduces the overall cost of products, improves production efficiency, and has good environmental protection.
Smart Images

Figure CN118970240B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of battery formation, in particular to an internal formation process of a colloidal battery. Background Art
[0002] Lead-acid batteries are characterized by low price, mature technology, stable performance, and recycling. At this stage, green and low-carbon have become the keywords for high-quality industrial development in China and even the world. The innovation of new power systems based on new energy, accompanied by the continuous improvement of deep cycle technology, will continue to drive the more widespread application of lead-acid batteries. Therefore, for a long time to come, lead-acid batteries will still occupy the largest share in the secondary power supply market. Colloidal lead-acid batteries are widely used in communication systems, power systems, new energy storage and other fields due to their good cycle life, good deep discharge recovery performance, and strong adaptability to temperature.
[0003] At present, the production of colloidal batteries by various manufacturers is still stuck in the state of 20 years ago, without any technological innovation: using external plates to form the battery, or using green plates to assemble the battery, adding acid to charge and form, then pouring acid, and then pouring colloidal. Both of the above methods have complicated processes, and a large amount of waste acid is generated during the process, which puts huge pressure on the environment and management costs. Therefore, it is of great significance to scientifically design to shorten the process flow, reduce intermediate processes, reduce the overall cost of products, and study the colloidal formula of colloidal batteries directly formed internally. Summary of the invention
[0004] The object of the present invention is to provide a colloidal battery internal formation process, which can.
[0005] To achieve the above object, the technical solution adopted by the present invention is:
[0006] A colloid battery internal formation process, which adopts vacuum infusion to add acid-containing colloid electrolyte, and after standing, adopts low current density formation and constant voltage charging to perform internal formation; wherein: a sheet-type felt PVC separator with an S-shaped channel surface on the back is used between the positive plate and the negative plate in the pole group, the S-shaped channel surface of the sheet-type felt PVC separator faces the negative plate and the felt surface faces the positive plate, and an electrolyte diffusion channel is formed between the bottom of the pole group and the bottom of the battery shell through pads.
[0007] Preferably, the acid-containing colloidal electrolyte comprises the following components in parts by weight: 18-25 parts of 20% nano-silicon dioxide solution, 28-32 parts of 1.4 g / mL sulfuric acid, and 0.4-0.6 parts of anhydrous sodium sulfate. After the acid-containing colloidal electrolyte is prepared, vacuum perfusion is performed within 30 minutes.
[0008] Preferably, the particle size of the nano-silicon dioxide is 7nm-40nm.
[0009] Preferably, the preparation process of the acid-containing colloidal electrolyte is: first dissolving anhydrous sodium sulfate in sulfuric acid to obtain liquid A, then storing liquid A and nano-silicon dioxide solution in an environment of 8-10°C for more than 8 hours, and finally mixing and stirring liquid A and nano-silicon dioxide solution at a high speed to obtain the acid-containing colloidal electrolyte.
[0010] Preferably, the acid-containing colloidal electrolyte has a viscosity of 16 mPa·s-20 mPa·s at 10°C and a density of 1.260±0.005 g / mL at 20°C.
[0011] Preferably, the process parameters of the vacuum infusion are: vacuum time 12-15 seconds, venting time 6-8 seconds, vacuum times 3-5 times, and vacuum pressure 0.08±0.005MPa.
[0012] Preferably, the standing time is 2-4 hours, and the internal temperature of the battery is controlled to be lower than 50° C. by water circulation.
[0013] Preferably, the internal formation is carried out in a water bath throughout the whole process, and the plate formation stage of eight-charge and two-discharge and the gel reshaping stage of two-charge and two-discharge are carried out in sequence. The plate formation stage adopts a charging mode combining constant current and reduced formation current density and controls the overall current density at 5.5 mA / cm 2 The following; the gel reshaping stage realizes the gel forming through two deep discharges and low voltage constant voltage charging, and the colloidal electrolyte forms a gel without hydration.
[0014] Preferably, the plate formation stage comprises the following steps in sequence:
[0015] First charging process: current density 4.0±0.1mA / cm 2 , time 1±0.5 hours, battery internal temperature 35℃-45℃;
[0016] Secondary charging process: current density 5.45±0.05mA / cm 2 , time 16±0.5 hours, battery internal temperature 35℃-45℃;
[0017] Three-charge process: current density 4.1±0.1mA / cm 2 , time 8±0.5 hours, battery internal temperature 35℃-45℃;
[0018] Four-charge process: current density 2.0±0.1mA / cm 2 , time 8±0.5 hours, battery internal temperature 35℃-45℃;
[0019] First discharge process: current density 5.0±0.1mA / cm 2 , time 2±0.5 hours;
[0020] Five-charge process: current density 5.45±0.05mA / cm 2 , time 6±0.5 hours, battery internal temperature 35℃-45℃;
[0021] Six-charge process: current density 3.0±0.1mA / cm 2 , time 10±0.5 hours, battery internal temperature 40℃-50℃;
[0022] Second discharge process: current density 5.1±0.1mA / cm 2 , time 2.5±0.5 hours;
[0023] Seven charging steps: current density 5.45±0.05mA / cm 2 , time 4±0.5 hours, battery internal temperature 35℃-45℃;
[0024] Eight-charge process: current density 3.0±0.1mA / cm 2 , time 12±0.5 hours, battery internal temperature 40℃-50℃;
[0025] Preferably, the gel reshaping stage comprises the following steps in sequence:
[0026] Three-discharge process: current density 5.13±0.05mA / cm 2 , time 3±0.5 hours;
[0027] Nine-charge process: current density 5.47±0.05mA / cm 2 , time 10±0.5 hours, battery internal temperature 35℃-45℃; constant voltage 2.3V / cell;
[0028] Four-discharge process: current density 5.8±0.05mA / cm 2 , time 4.5±0.5 hours;
[0029] Ten-charge process: current density 5.5±0.05mA / cm 2 , time 12±0.5 hours, battery internal temperature 35℃-45℃; constant voltage 2.35V / cell;
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] The primary particles of nano-silica solution are Si-O-Si in structure and are spherical. On their surface, hydroxyl-OH interacts to form chain-like secondary particles. When the silanol groups between the particles combine with hydrogen bonds to form a three-dimensional structure polymer, the viscosity of the silica solution increases. The sulfuric acid solution contains a large number of hydrogen ions and hydrogen sulfate ions, and the activity of hydrogen ions becomes more active with the increase of temperature. As a result, when preparing the acid-containing colloidal electrolyte, it is necessary to control the temperature of the raw materials and use external forces (such as stirring shear force, etc.) to stir strongly to destroy the three-dimensional structure and make the medium thinner. Therefore, when preparing the acid-containing colloidal electrolyte, the raw sulfuric acid and silica solution need to be frozen to 8-10°C, and a mixer is used for high-speed mixing and stirring to destroy the three-dimensional structure of the gel and make it thinner, thereby achieving vacuum addition of glue.
[0032] After the acid-containing colloidal electrolyte is added to the battery, the three-dimensional structure of the gel will slowly recover after the stirring external force disappears. The acid-containing colloidal electrolyte begins to thicken and increase in viscosity. At this time, the use of the pole group pad forms an electrolyte diffusion channel between the pole group and the bottom of the battery shell. The acid-containing colloidal electrolyte diffuses evenly along the four sides of the pole plate to the center of the pole plate during the infusion process. The temperature rise of the gel electrolyte during the diffusion process can be effectively reduced by freezing it to 8-10°C. Delaying the gel time is conducive to the diffusion of the gel electrolyte to the center of the pole group, avoiding the phenomenon that the acid-containing colloidal electrolyte cannot diffuse in place due to the thickening of the acid-containing colloidal electrolyte and ultimately does not form a gel. After the formation is completed, it can be clearly seen that the gel forms a complete gel at the bottom of the pole group.
[0033] When sulfuric acid in the acid-containing colloidal electrolyte comes into contact with the green plate, a violent chemical reaction occurs rapidly and a large amount of heat is released. The temperature inside the battery rises rapidly, and the gas in the separator is squeezed and escapes. The felt surface of the sheet-type felt PVC separator is used to cover the positive electrode, and the S-shaped channel surface is facing the negative electrode, so that the gel forms along the S-shaped channel surface, thereby squeezing the gas in the separator and quickly discharging upward along the felt surface. Therefore, the battery is placed in a water cycle for cooling, which reduces the temperature inside the battery and allows the generated gas to be fully discharged, so that the acid-containing colloidal electrolyte initially forms a gel in the pole group.
[0034] The present invention controls the overall current density at 5.5 mA / cm during the plate formation stage. 2In the following, a charging mode combining constant current and reduced formation current density is adopted, which can not only realize the internal formation of the plate but also control the temperature during the formation process to a limited extent; in the gel re-forming stage, two deep discharges and low voltage constant voltage charging are used to realize the formation of the gel, and a constant voltage of 2.3V / cell is used in the nine-charge stage. At this time, there is basically no oxygen generation during the positive electrode charging process, which prolongs the gel time. After adopting the internal formation technical solution of the present invention, the colloidal electrolyte forms a gel without hydration, the gel at the top of the pole group is jelly-like, the gel on the side of the pole group is fixed and has no flow, and the gel is formed around the pads at the bottom of the pole group. The gel acid density is 1.30g / mL-1.33g / mL, and the gel content is 12%-15%.
[0035] The present invention realizes direct injection of gel electrolyte into the colloid battery, improves production efficiency, and realizes zero waste acid discharge without acid replacement, thus achieving clean and environmentally friendly production. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 The figure is a process flow chart of the internalization of the colloidal battery of the present invention.
[0037] Figure 2 This is a diagram showing the effect of internalization into the top gel of the posterior pole group of the present invention.
[0038] Figure 3 This is a side gel effect diagram of the internalization into the posterior pole group of the present invention.
[0039] Figure 4 This is a diagram showing the effect of internalization into the top gel of the posterior pole group of the present invention.
[0040] Figure 5 This is a diagram showing the internalization effect of the positive electrode plate of the present invention. DETAILED DESCRIPTION
[0041] In order to make the above features and advantages of the present invention more obvious and easy to understand, embodiments are given below with reference to the accompanying drawings for detailed description as follows.
[0042] like Figure 1 As shown, this embodiment provides a colloidal battery internal formation process, including pole group plate packaging and shelling, acid-containing colloidal electrolyte preparation, vacuum infusion, static and internal formation, wherein the internal formation adopts a combination of low current density formation and constant voltage charging to sequentially carry out eight-charge-two-discharge pole plate formation stage and two-charge-two-discharge gel reshaping stage, the internal formation is carried out in a water bath throughout the process, the pole plate formation stage adopts a charging mode combining constant current and reduced formation current density and controls the overall current density at 5.5 mA / cm 2 The following; the gel reshaping stage realizes the gel forming through two deep discharges and low voltage constant voltage charging, and the colloidal electrolyte forms a gel without hydration.
[0043] Among them: in the process of packing and shelling the pole group, the pole group is composed of a positive plate, a negative plate and a separator. The separator adopts a sheet-type felt PVC separator. The front of the sheet-type felt PVC separator is a felt surface and the back forms an S-shaped channel surface. The felt surface faces the positive plate, and the S-shaped channel surface faces the negative plate. In addition, the bottom of the pole group, i.e., the bottom of the positive plate and the bottom of the negative plate, respectively, form an electrolyte diffusion channel with the bottom of the battery shell through pads, and the height of the pads is 4mm.
[0044] Wherein: in the preparation process of the acid-containing colloidal electrolyte, the acid-containing colloidal electrolyte includes the following weight-part array components: 20 parts of 20% nano-silicon dioxide solution, 30 parts of 1.4g / mL sulfuric acid, and 0.45 parts of anhydrous sodium sulfate, and the particle size of the nano-silicon dioxide is 7nm-40nm. The preparation process is: first dissolve anhydrous sodium sulfate in sulfuric acid to obtain liquid A, then store liquid A and nano-silicon dioxide solution in an environment of 8-10℃ for more than 8 hours, and finally mix and stir liquid A and nano-silicon dioxide solution at a stirring speed of 800r / min to obtain an acid-containing colloidal electrolyte. The physical properties of the acid-containing colloidal electrolyte: the viscosity at 10℃ is 18.2mPa•s, and the density at 20℃ is 1.262g / mL; the gel strength is that after standing for 24h, a 0.5g lead ball falls from a height of 20cm, and the depth of the ball falling into the gel is less than 5mm.
[0045] Among them: in the vacuum infusion process, the acid-containing colloidal electrolyte is prepared and vacuum infused within 30 minutes, and the process parameters are: vacuum time 15 seconds, venting time 7 seconds, vacuum times 3 times, and vacuum pressure 0.08MPa.
[0046] Among them: in the standing and internal formation process, after the vacuum infusion is completed, it should be stood for 2-4 hours (4 hours in this embodiment), and the internal temperature of the battery is controlled to be lower than 50° C. by water circulation. The process conditions of the plate formation stage and the gel reshaping stage are shown in Table 1.
[0047] Table 1: Process parameters of the internalization process of this embodiment
[0048]
[0049] Processes 1-10 in the table belong to the plate formation stage, during which the overall current density is controlled at 5.5 mA / cm 2In the following, a charging mode combining constant current and reduced formation current density is adopted, which can not only realize the internal formation of the plate but also control the temperature during the formation process to a limited extent; processes 11-14 belong to the gel re-forming stage. As the discharge proceeds, the three-dimensional gel structure of the colloidal electrolyte inside the battery will slowly recover and form a gel again; a constant voltage of 2.3V / cell is adopted in the supplementary power stage. At this time, basically no oxygen is generated during the positive electrode charging process, which prolongs the gel time; the gel formation is achieved through two deep discharges and low-voltage constant-voltage charging.
[0050] After adopting the above internalization technology solution, the gel on the top of the pole group becomes jelly-like, the gel on the side of the pole group is fixed and does not flow, and gel is formed around the pads at the bottom of the pole group. Figure 2-4 As shown. For the formation effect of the positive plate, see Figure 5 .
[0051] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for illustrating the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which shall fall within the scope of the present invention to be protected. The scope of protection of the present invention shall be defined by the attached claims and their equivalents.
Claims
1. A colloidal battery internal formation process, characterized in that: The internal formation process includes electrode group plate packaging and shell placement, acid-containing colloidal electrolyte preparation, vacuum infusion, static placement and internal formation; wherein: In the process of packing and shelling the pole group, the pole group is composed of a positive plate, a negative plate and a separator. The separator adopts a sheet-type felt PVC separator. The front side of the sheet-type felt PVC separator is a felt surface and the back side forms an S-shaped channel surface. The felt surface faces the positive plate, and the S-shaped channel surface faces the negative plate. An electrolyte diffusion channel is formed between the bottom of the pole group and the bottom of the battery shell through the pads. In the step of preparing the acid-containing colloidal electrolyte, the acid-containing colloidal electrolyte comprises the following components in weight: 18-25 parts of 20% nano-silicon dioxide solution, 28-32 parts of 1.4g / mL sulfuric acid, and 0.4-0.6 parts of anhydrous sodium sulfate. After the acid-containing colloidal electrolyte is prepared, vacuum perfusion is performed within 30 minutes; The preparation process of the acid-containing colloidal electrolyte is as follows: firstly, anhydrous sodium sulfate is dissolved in sulfuric acid to obtain liquid A, then liquid A and nano-silicon dioxide solution are stored in an environment of 8-10° C. for more than 8 hours, and finally liquid A and nano-silicon dioxide solution are mixed and stirred at a high speed to obtain the acid-containing colloidal electrolyte; In the vacuum infusion process, the acid-containing colloidal electrolyte is added by vacuum infusion; In the static and internal formation process, the static time is 2-4 hours, and the internal temperature of the battery is controlled to be lower than 50°C by water circulation. The internal formation is carried out in a water bath throughout the whole process, and the plate formation stage of eight charges and two discharges and the gel reshaping stage of two charges and two discharges are carried out in sequence. The plate formation stage adopts a charging mode combining constant current and reduced formation current density and controls the overall current density at 5.5 mA / cm 2 The following: The gel reshaping stage is achieved by two deep discharges and low voltage constant voltage charging to form the gel, and the colloidal electrolyte forms a gel without hydration; The plate formation stage includes the following steps in sequence: First charging process: current density 4.0±0.1mA / cm 2 , time 1±0.5 hours, battery internal temperature 35℃-45℃; Secondary charging process: current density 5.45±0.05mA / cm 2 , time 16±0.5 hours, battery internal temperature 35℃-45℃; Three-charge process: current density 4.1±0.1mA / cm 2 , time 8±0.5 hours, battery internal temperature 35℃-45℃; Four-charge process: current density 2.0±0.1mA / cm 2 , time 8±0.5 hours, battery internal temperature 35℃-45℃; First discharge process: current density 5.0±0.1mA / cm 2 , time 2±0.5 hours; Five-charge process: current density 5.45±0.05mA / cm 2 , time 6±0.5 hours, battery internal temperature 35℃-45℃; Six-charge process: current density 3.0±0.1mA / cm 2 , time 10±0.5 hours, battery internal temperature 40℃-50℃; Second discharge process: current density 5.1±0.1mA / cm 2 , time 2.5±0.5 hours; Seven charging steps: current density 5.45±0.05mA / cm 2 , time 4±0.5 hours, battery internal temperature 35℃-45℃; Eight-charge process: current density 3.0±0.1mA / cm 2 , time 12±0.5 hours, battery internal temperature 40℃-50℃; The gel reshaping stage comprises the following steps in sequence: Three-discharge process: current density 5.13±0.05mA / cm 2 , time 3±0.5 hours; Nine-charge process: current density 5.47±0.05mA / cm 2 , time 10±0.5 hours, battery internal temperature 35℃-45℃; constant voltage 2.3V / cell; Four-discharge process: current density 5.8±0.05mA / cm 2 , time 4.5±0.5 hours; Ten-charge process: current density 5.5±0.05mA / cm 2 , time 12±0.5 hours, battery internal temperature 35℃-45℃; constant voltage 2.35V / cell.
2. The internal formation process of the colloidal battery according to claim 1, characterized in that: The particle size of the nano silicon dioxide is 7nm-40nm.
3. The internal formation process of the colloidal battery according to claim 1, characterized in that: The acid-containing colloidal electrolyte has a viscosity of 16 mPa·s-20 mPa·s at 10°C and a density of 1.260±0.005 g / mL at 20°C.
4. The internal formation process of the colloidal battery according to claim 1, characterized in that: The process parameters of the vacuum infusion are: vacuum time 12-15 seconds, venting time 6-8 seconds, vacuum times 3-5 times, and vacuum pressure 0.08±0.005MPa.
Citation Information
Patent Citations
Colloid lead acid battery inner formation method
CN104900923A
Gel battery container formation gel electrolyte, preparation method and container formation process
CN116914280A
Container formation process for lead-acid colloid storage battery
CN118610604A